Effect of mycorrhiza and rhizobium on Phaseolus vulgaris L - Bhattarai, Nabin; Baral, Bikash; Shrestha, Geeta; Yami, Kayo Devi (Scientific World, 2011)
Study on effectiveness of Rhizobium leguminosarum (bv. phaseoli) inoculum and mycorrhiza on red kidney bean (Phaseolus vulgaris L.), locally called Rajma was carried out in pot experiment at Nepal Academy of Science and Technology (NAST) in 2008. The parameters evaluated to study the effectiveness of inoculum application were number of nodules, biomass, number of pods, root length, shoot length and dry seed weight. The study consisted of four treatments, Rhizobium, Mycorrhizal spores, fertilizer (DAP) and control which were replicated 4 times. Rhizobium inoculated plants showed higher dry biomass, longer root and shoot length, higher number of pods and maximum nodule formation of red kidney bean in comparison to other treatments which was statistically significant (P< 0.05). Those treatments which were treated with Rhizobium inoculum and fertilizer showed nearly the same weight of dry seed than other treatments which is followed by mycorrhiza and control. Hence Rhizobium and mycorrhza can be used as biofertilizer which is economically and environmentally friendly. Key words: Rhizobium; Mycorrhiza; Inoculum; Biofertilizer DOI: http://dx.doi.org/10.3126/sw.v9i9.5522 SW 2011; 9(9): 66-69